Colonial Entanglements and Ecological Power: Spice Commodification in Dune Movie (2021) - Prihatika, Yusrina Dinar (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This study examines the themes of colonial entanglement and ecological power in the film Dune (2021), focusing on the commodification of the spice